5(7)+7(2(7)+8)=x

Simple and best practice solution for 5(7)+7(2(7)+8)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7)+7(2(7)+8)=x equation:


Simplifying
5(7) + 7(2(7) + 8) = x

Multiply 5 * 7
35 + 7(2(7) + 8) = x

Multiply 2 * 7
35 + 7(14 + 8) = x

Combine like terms: 14 + 8 = 22
35 + 7(22) = x

Multiply 7 * 22
35 + 154 = x

Combine like terms: 35 + 154 = 189
189 = x

Solving
189 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
189 + -1x = x + -1x

Combine like terms: x + -1x = 0
189 + -1x = 0

Add '-189' to each side of the equation.
189 + -189 + -1x = 0 + -189

Combine like terms: 189 + -189 = 0
0 + -1x = 0 + -189
-1x = 0 + -189

Combine like terms: 0 + -189 = -189
-1x = -189

Divide each side by '-1'.
x = 189

Simplifying
x = 189

See similar equations:

| 15+2*25= | | sqrt(2x+26)-9=x | | 5x+7(2x+8)=189 | | -15+25*2= | | 23=9d+8d | | 5xy+25x^2y+10xy^2=0 | | x/3-6=21 | | f(x)=x^4+2x^2-x+3 | | 9x^2+8x+1=0 | | 6d-2d=10d+1 | | -6n+8-7n=25 | | -15+2*9= | | 9x=17-(-10) | | 63=x(x+2) | | 4.2z-5.17=8.438 | | 5w-15w=-30 | | x-5y+x-y=1228 | | 6(5+7c)=-16 | | 3x+8=16x+1+19 | | (-7-3)/5*6= | | 5-5(7+7)= | | (3+y)-40=7y | | x-5yandx-y=1228 | | U/3=11/7 | | 3u(u-1)=(3u+4)(u-5) | | -5(-3y+9)+y=-2 | | log(2x-1)+logx=2 | | c/9=81 | | 750+22n-264=650+30n-300 | | 12j^3+28=0 | | -5-2=-4+x | | 5x+7(2x+8)=179 |

Equations solver categories